2021
DOI: 10.3390/rs13020308
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Suitability of UAS-Based Multispectral Images for Estimating Soil Organic Carbon: Comparison with Proximal Soil Sensing and Spaceborne Imagery

Abstract: Soil organic carbon (SOC) is a variable of vital environmental significance in terms of soil quality and function, global food security, and climate change mitigation. Estimation of its content and prediction accuracy on a broader scale remain crucial. Although, spectroscopy under proximal sensing remains one of the best approaches to accurately predict SOC, however, spectroscopy limitation to estimate SOC on a larger spatial scale remains a concern. Therefore, for an efficient quantification of SOC content, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 86 publications
1
22
0
1
Order By: Relevance
“…It should be noted that the SOC variation in this study was relatively small compared to other studies using UAV‐based spectroscopy (Aldana‐Jague et al, 2016; Biney et al, 2021; Laamrani et al, 2019). The successful prediction of SOC using UAV‐derived spectra demonstrates an adequate performance and sensitivity of hyperspectral sensor to derive effective information from noisy signals (caused by surface disturbing conditions) given the fine spectral resolution, even when the variation range of the target variable is small.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…It should be noted that the SOC variation in this study was relatively small compared to other studies using UAV‐based spectroscopy (Aldana‐Jague et al, 2016; Biney et al, 2021; Laamrani et al, 2019). The successful prediction of SOC using UAV‐derived spectra demonstrates an adequate performance and sensitivity of hyperspectral sensor to derive effective information from noisy signals (caused by surface disturbing conditions) given the fine spectral resolution, even when the variation range of the target variable is small.…”
Section: Discussionmentioning
confidence: 58%
“…It should be noted that the SOC variation in this study was relatively small compared to other studies using UAV-based spectroscopy (Aldana-Jague et al, 2016;Biney et al, 2021;Laamrani et al, 2019).…”
Section: Capability Of Uav-borne Spectrometry For Soc Mappingmentioning
confidence: 70%
See 2 more Smart Citations
“…Zhou et al [36], Zhang et al [43], and Paul et al [44] used land use type as a variable to predict SOC content, but the results showed that it did not contribute much to the model. In recent studies, remote sensing data were used to predict SOC content based on multiple land use types, while the results showed that the accuracy of SOC prediction using satellite remote sensing data was lower than that using airborne remote sensing and laboratory reflectance spectra data [19,45]. Therefore, it is possible to improve the prediction accuracy of SOC based on satellite remote sensing data under a single land use type.…”
Section: Introductionmentioning
confidence: 99%